Gender, mental health, and psychiatric institution in the work of Franca Ongaro Basaglia (Phenomenology, Humanities and Sciences, 2025)
Franca Ongaro Basaglia was one of the leaders of the de-institutionalization movement for psychiatric patients in Italy, known as Democratic Psychiatry, and she was a major influence on the Brazilian model of Psychosocial Care with its Psychosocial Care Centers. Given the impact of her intellectual production and political action on the mental health landscape in Brazil, it is noteworthy that Franca remains largely unknown to the national public, overshadowed by her partner Franco Basaglia. This article aims to present and discuss the work of Franca Ongaro Basaglia based on the book Mujer, Locura y Sociedad, focusing on three central themes in her production: the psychiatric institution, the understanding of gender, and women's mental health. As a reflection, based on Franca's case, the article discusses the epistemic erasure of women as authors of science and the constitution of scientific authority.
Keywords: desinstitucionalization; woman; Democratic psychiatry